Molecular modelling of vitamin B12 and its analogues - Govender, Penny, author.
1 online resource
Keywords: For many years, the chemistry of vitamin B12 and its derivatives has been investigated for their inherent eco-friendly and nontoxic nature. This vitamin, also known as cobalamin, is an organic complex that contains a cobalt ion in its structure. Its derivatives are vital bio-inorganic cofactors and possess complex and rich photolytic properties, facilitated by their excited states. This book compiles and details cutting-edge research in the application of vitamin B12 as an environmentally benign catalyst for several organic reactions. It discusses the recent advances and current understanding of the photolytic properties of vitamin B12 derivatives from the perspective of the density functional theory (DFT). The book is of interest for anyone involved in nanotechnology, macromolecular science, cancer, and drug-delivery research.